Using Centromere Mediated Genome Elimination to Elucidate the Functional Redundancy of Candidate Telomere Binding Proteins in Arabidopsis thaliana - Fulcher, Nick; Riha, Karel (Frontiers in Genetics, 2016)
Proteins that bind to telomeric DNA form the key structural and functional constituents of telomeres. While telomere binding proteins have been described in the majority of organisms, their identity in plants remains unknown. Several protein families containing a telomere binding motif known as the telobox have been previously described in Arabidopsis thaliana. Nonetheless, functional evidence for their involvement at telomeres has not been obtained, likely due to functional redundancy. Here we performed genetic analysis on the TRF-like family consisting of six proteins (TRB1, TRP1, TRFL1, TRFL2, TRFL4 and TRF9) which have previously shown to bind telomeric DNA in vitro. We used haploid genetics to create multiple knock-out plants deficient for all six proteins of this gene family. These plants did not exhibit changes in telomere length, or phenotypes associated with telomere dysfunction. This data demonstrates that this telobox protein family is not involved in telomere maintenance in Arabidopsis. Phylogenetic analysis in major plant lineages revealed early diversification of telobox proteins families indicating that telomere function may be associated with other telobox proteins.